2020
DOI: 10.1016/j.athoracsur.2019.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Thoracic Surgery Social Media Network: Early Experience With TweetChat-Based Journal Clubs

Abstract: Background. Virtual journal clubs on Twitter (TweetChats) provide a platform to globally discuss publications. The Thoracic Surgery Social Media Network (TSSMN) is an organization that focuses on bringing social media attention to key publications in cardiothoracic surgery. TSSMN recently formed a Trainee Group with the goal of conducting chats covering key topics in cardiothoracic surgical training. The aim of this study was to characterize the pilot experience of this group.Methods. The TSSMN trainee group h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(17 reference statements)
0
16
0
Order By: Relevance
“… 18 Broadcasting journal clubs through social media has been successful in reaching larger audiences. 19 Similar opportunities arise for educational groups, such as the Thoracic Education Cooperative Group, to expand their networks into the virtual world. 20 Context-specific learning: Virtual learning may enable similar programs (eg, geographic based on ethnical and genetic variations or resource constraints) to share lessons and find common solutions to specific patient problems or institutional barriers.…”
Section: The Possibilitiesmentioning
confidence: 94%
See 1 more Smart Citation
“… 18 Broadcasting journal clubs through social media has been successful in reaching larger audiences. 19 Similar opportunities arise for educational groups, such as the Thoracic Education Cooperative Group, to expand their networks into the virtual world. 20 Context-specific learning: Virtual learning may enable similar programs (eg, geographic based on ethnical and genetic variations or resource constraints) to share lessons and find common solutions to specific patient problems or institutional barriers.…”
Section: The Possibilitiesmentioning
confidence: 94%
“… 18 Broadcasting journal clubs through social media has been successful in reaching larger audiences. 19 Similar opportunities arise for educational groups, such as the Thoracic Education Cooperative Group, to expand their networks into the virtual world. 20 …”
Section: The Possibilitiesmentioning
confidence: 94%
“…3 . The influence of two tweet-based global surgery journal clubs on the volume of posts is clear on 2/6/19 and 2/19/19, further stressing the role that top posters play in the discussion around global surgery [ 13 ]. Of note, there were three captured monthly online Twitter Journal Club sessions specifically led and created regarding global surgery, leading to increased participation and activity within the global surgery social media community.…”
Section: Resultsmentioning
confidence: 99%
“…This collaborative virtual group formed by the joint efforts of The Annals of Thoracic Surgery and The Journal of Thoracic and Cardiovascular Surgery has 18 delegates and collectively over 53,000 followers. The TSSMN has been successful in bringing together medical professionals and trainees at all levels across the world for networking and dissemination of topical journal articles in the field of cardiothoracic surgery via TweetChatbased journal clubs (35). Additionally, recent results from a randomized trial demonstrated significantly improved Altmetric scores, Mendeley reads, and Twitter impressions when articles were tweeted versus control (non-tweeted), suggesting that this academic dialogue is impactful and long-lasting (36).…”
Section: Social Media For Surgeonsmentioning
confidence: 99%